ChemInform Abstract: Antioxidant Flavone Glycosides and Other Constituents from Premna latifolia Leaves. Issue 48 (2nd December 2014) - Ghosh, Partha Sarathi; Das, Niranjan; Dinda, Biswanath
Abstract The new flavone glycoside (I) is isolated along with two known compounds from the leaves of the medicinal plant, Premna latifolia Roxb (Verbenaceae).